1989
DOI: 10.1016/0014-5793(89)80424-7
|View full text |Cite
|
Sign up to set email alerts
|

Reductive chain separation of botulinum A toxin — a prerequisite to its inhibitory action on exocytosis in chromaffin cells

Abstract: Cleavage of the disulfide bond linking the heavy and the light chains of tetanus toxin is necessary for its inhibitory action on exocytotic release of catecholamines from permeabilized chromaffin cells [(1989) FEBS Lett. 242, 245-248; J. Neurochem., in press]. The related botulinum A toxin also consists of a heavy and a light chain linked by a disulfide bond. The actions of both neurotoxins on exocytosis were presently compared using streptolysin 0-permeabilized bovine adrenal chromaffin cells. Botulinum A tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Interestingly the molecular weight of the SNAP-25 immunoreactive band in the blots was about 60 kDa, that is about 35 kDa larger than that of authentic SNAP-25. We harvested the chromaffin vesicle fractions (11)(12)(13)(14) from the sucrose gradients, isolated their membranes (see Section 2), and analyzed them further. Again, in unboiled samples the anti-SNAP-25 antibody labelled a band of 60 kDa (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly the molecular weight of the SNAP-25 immunoreactive band in the blots was about 60 kDa, that is about 35 kDa larger than that of authentic SNAP-25. We harvested the chromaffin vesicle fractions (11)(12)(13)(14) from the sucrose gradients, isolated their membranes (see Section 2), and analyzed them further. Again, in unboiled samples the anti-SNAP-25 antibody labelled a band of 60 kDa (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Absorbance at 280 nm after precipitation of the protein with 10% (w/v) TCA was measured to conveniently locate chromaffin vesicles in the gradient while arylsulfatase served to identify fractions containing lysosomes and other subcellular membranes [26]. The fractions enriched in chromaffin vesicles (fractions [11][12][13][14] were recovered from the gradient, diluted 1:4 with 20 mM MOPS (pH 7.0), 5 mM EDTA and centrifuged for 1 h at 100 000 x g. The purified chromaffin vesicles were osmotically lysed by addition of a 10-fold excess of 20 mM MOPS (pH 7.0) with 5 mM EDTA. Chromaffin vesicle membranes were recovered by centrifugation for 1 b at 100000xg and washed twice in potassium glutamate medium (see above) containing 6 mM magnesium acetate.…”
Section: Purification Of Chromaffin Vesicle Membranes and Incubation mentioning
confidence: 99%
See 1 more Smart Citation
“…21 In these neuroendocrine cells reductive conditions enhance the inhibitory effect on catecholamine secretion of the two-chain form of botulinum A toxin. 20 Furthermore, the light chain alone is fully active. 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Chromaffin cells express all three neurotoxin substrates [17,18] which can be isolated in a complex [18] and Ca2+-dependent exocytosis in these cells is sensitive to neurotoxins that target VAMP (tetanus and botulinum B neurotoxins) [19][20][21][22][23][24] or SNAP-25 (botulinum A and E neurotoxins) [23,[25][26][27][28]. Insulin-secreting cells are also sensitive to these two classes of neurotoxins [29][30][31] and studies on these cells have suggested that VAMP is essential for Ca2+-induced secretion but not for insulin release activated by the non-hydrolysable GTP analogue, GTPTS, since this was insensitive to tetanus toxin and botulinum B neurotoxin [29].…”
Section: Introductionmentioning
confidence: 99%